2008
DOI: 10.1063/1.3031701
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the low frequency noise in indium arsenide nanowire transistors

Abstract: Low-frequency noise in strained SiGe core-shell nanowire p-channel field effect transistors Appl. Phys. Lett. 97, 073505 (2010); 10.1063/1.3480424High-performance, fully transparent, and flexible zinc-doped indium oxide nanowire transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Other studies on advanced structures with comparable gate length, though including more measured devices, show up to five orders of magnitude in variation [7]. As a reference, we also measured the LFN for devices with varying number of nanowires (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), where we observed the CNSD level to decrease slightly as the number of wires was increased. In Figure 2b, CNSD for NW 1 and 2 is plotted versus the drain current at a constant frequency of 10 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies on advanced structures with comparable gate length, though including more measured devices, show up to five orders of magnitude in variation [7]. As a reference, we also measured the LFN for devices with varying number of nanowires (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), where we observed the CNSD level to decrease slightly as the number of wires was increased. In Figure 2b, CNSD for NW 1 and 2 is plotted versus the drain current at a constant frequency of 10 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study of similar Si NWs show values of about 5x10 -10 Hz -1 for L g = 350 nm at 10 Hz and 1 µA [13]. From a LFN temperature study of lateral InAs NWs with SiO 2 gate oxide (back-gated) and 2 µm gate length, we extrapolated the minimum normalized CNSD at 10 Hz (data taken at 250 K), to be about 1x10 -7 Hz -1 [8]. Another study of an AlSb/InAs HEMT show, for L g = 100 nm, by us extrapolated value at 10 Hz, a minimum of 3x10 -10 Hz -1 [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In a study of 30 nm wide InAs NWs with L G ¼ 2 lm (SiO 2 dielectric), a H was measured as a function of temperature and for a low temperature, T ¼ 2 K, a H ¼ 5 Â 10 À4 was obtained. 14 The value was referred to as a lower bound for one-and two-dimensional InAs systems and this was argued on the basis that other studies reported similar lowest values. Two other studies of InAs NW FETs; one with 40-nm-diameter NWs and L G ¼ 35 nm (HfO 2 dielectric), 9 and one with 27-nm-diameter NWs and L G ¼ 100-750 nm (Al 2 O 3 dielectric), 15 report values of a H ¼ 4 Â 10 À3 and a H $ 10 À3 , respectively.…”
mentioning
confidence: 99%
“…In this work, we successfully synthesized high-quality InAs NWs through a convenient CVD process [16][17][18], and systematically studied the diameter-dependent thermal conductivity of InAs NWs in air by a simple laser heating method. The obtained thermal conductivity of InAs NWs lies in the range of 6.4-10.5 W m -1 K -1 depending on their diameters, and presents a monotonic increase with increasing diameter, which agrees well with the previously reported results.…”
Section: Introductionmentioning
confidence: 99%